The impact of climatic variation on the Boran pastoral system - Cossins, N.J.; Upton, M. (Elsevier, 1988)
Discusses the variation in rainfall and its implications for the length of growting season and consequent dry matter production from the East African rangelands. Presents evidence of the effects of primary dry-matter production on livestock performance. Describes shifts in the relative prices of livestock and cereals and the overall impact on pastoralist food consumption. Discusses some possible approaches to the mitigation of drought effects.